Development of a water desalinator low cost solar heating - Pinto, Leandro Ferreira; Silva, Diogo Italo Segalen; Mantovani, Daniel; Moura, Marcos Antônio Lima; Carvalho, Sandra Helena Vieira; Soletti, João Inácio (Revista Tecnológica, 2014)
Approximately two thirds of the land surface is covered with water, with 97% salt, the remainder, only 1% can be used for human consumption. An alternative to the use of drinking water is desalination of salt water using solar energy. Desalination can be applied to sea water (total dissolved solids ≥ 30.000 mg/L) as the brackish water from wells, (total dissolved solids between 500 and 30.000 mg/L). This study investigated the effect of operating variables and design of a desalination unit for brackish water, low cost, for family use, that meets the communities of the semi-arid areas. The variables studied and were related to climatic conditions: high water level, water salinity and solar radiation. The experiments were performed at a latitude of 9°3’ South and longitude 35° 35’ west, in Maceió, Alagoas. Production was obtained from 2.5 litres/m2 of distilled water per day.